2020
DOI: 10.1111/aec.12996
|View full text |Cite
|
Sign up to set email alerts
|

Elevational shifts in phylogenetic diversity of angiosperm trees across the subtropical Brazilian Atlantic Forest

Abstract: Elevation gradients are drivers of species diversity, and, recently, studies have considered the evolutionary process in shaping community assembly patterns. Patterns of plant species richness across elevational gradients have been studied in different parts of the Atlantic Forest; however, little is known about plant phylogenetic diversity patterns. Thus, we aimed to analyse the phylogenetic diversity of angiosperm trees along an elevation gradient in southern Brazilian Plateau, in the subtropical portion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 71 publications
(154 reference statements)
0
9
2
1
Order By: Relevance
“…Meanwhile, most Rubiaceae clades have a complex biogeographic history, and their high diversity in South America seems to be linked to the rise of the Andes ( 74 ). Families like Myrtaceae and Lauraceae are more commonly found in moist environments and, in South America, have acquired adaptations to colder temperatures, enabling them to diversify in higher elevations ( 75 ), which could explain their high diversity in South America and low diversity in Africa. In contrast, Ebenaceae, particularly the genus Diospyros, is known for its morphological and species diversity in Africa, coupled with a geographically wide distribution ( 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, most Rubiaceae clades have a complex biogeographic history, and their high diversity in South America seems to be linked to the rise of the Andes ( 74 ). Families like Myrtaceae and Lauraceae are more commonly found in moist environments and, in South America, have acquired adaptations to colder temperatures, enabling them to diversify in higher elevations ( 75 ), which could explain their high diversity in South America and low diversity in Africa. In contrast, Ebenaceae, particularly the genus Diospyros, is known for its morphological and species diversity in Africa, coupled with a geographically wide distribution ( 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Observations to date provide mixed support for the TNC, OTT, and OTL hypotheses: latitudinal decreases in evolutionary diversity (Kerkhoff et al, 2014) and angiosperm family ages (Hawkins et al, 2011;Romdal et al, 2013) have been reported, but also an increase in basal−weighted phylogenetic beta diversity to high latitudes (McFadden et al, 2019). Evolutionary diversity has been found to decrease with elevation in tropical montane forest (Bergamin et al, 2020), but also to increase along with increasing family age (Qian et al, 2014;Tiede et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…In Australasia, Myrtaceae predominate in most ecosystems, with more than 2250 species recorded [1]. They are also found in biological hotspots around the globe [2,3]. As such, A. psidii infection is a threat to many fragile ecosystems characterised by a high rate of endemism [4][5][6].…”
Section: Introductionmentioning
confidence: 99%